Analiza mladja na Pahernikovi posesti - Rihter, Tomaž (Acta silvae et ligni, 2024)
High-quality natural regeneration is the key to close-to-nature management, but forest inventories often fail to provide sufficient information. In 2023, we conducted additional sampling of regeneration in a network of permanent sampling plots on the Pahernik property. We found acceptable average densities for seedlings below 130 cm height, with 15,924 individuals ha-1, less satisfactory densities for saplings above 130 cm height and < 5 cm diameter, with 994 individuals ha-1, and low densities for saplings between 5 and 10 cm diameter, with 276 individuals ha-1. On average, regeneration covered 24% of the forest floor, while ground vegetation covered 11%. There were no major differences in regeneration density and cover between elevations and spatially separated parts of the property. The regeneration was dominated by Norway spruce (38%), followed by silver fir (32%) and beech (26%). The high proportion of silver fir was due to its high densities in the height class up to 20 cm. In the higher classes, silver fir was less represented and increasingly browsed by ungulates. The average browsing rate of regeneration up to 1.3 m was 33%, and specifically for silver fir, 39%. This study indicates possibilities for improving the forest inventory.
Keywords: gostota in zmes drevesnih vrst; gozdna inventura; jelovja; poškodbe mladovja; smrekovo-jelovo-bukovi gozdovi; veliki rastlinojedi parkljarji